Medicinal Plants and Radionuclides: A Review - T.S, Giani, (Pharmacognosy Reviews)
Medicinal plants and/or phytopharmaceuticals include flavonoids, terpens, saponins, tannins, alkaloids, glycosides, resins, volatile oils, and others compounds that provide various effects on human body: positive or not. Biocomplex of natural plants are common used in Nuclear Medicine and their effects on radionuclides are insufficient knowledge. The natural products and synthetic drugs can make effects on exams of Single Positron Emission Tomography – SPECT shows false prognostic. Synthetic drugs as anaesthetic sodium Phenobarbital, an Amantadine, Vincristine, Mitomycin-C, an Acetaminophen, Acetylsalicylic acid and Dipyrone (antipyretic and analgesics drugs), an antiseizure drugs, a Glucantime, Zinc-oxid-eugene, Phytic acid, others, and natural products as an extract of Cauliflower, Buzhong yi qi wan complex, Propolis, Uncaria tomentosa, Mentha crispa, Psidium guajava, Maytenus ilicifolia, Matricaria recutita, Thuya occidentalis, Paullinia cupana, Harpagophytum procumbens, Solanum melongena, Cinnamomum zeylanicum, Cymbopogoncitratus, Maytenus ilicifolia, Baccharis genistelloides, tobacco, and foods as a tomato, Punica granatum, Sechium edule, clove, and others, shows effects on the radionuclides and their reductors stannous chloride. Here, we discuss the effects of these plants/phyto-pharmaceuticals/synthetic drugs and their compounds on the labeling of red blood cells by sodium pertecnetate, their mechanism of action, and applications of the Nuclear Medicine.
Keywords: Nuclear Medicine; Phytopharmaceuticals; Radionuclides; Sodium pertecnetate; Medicinal plants